Efficient Public Participation in the Local Law-Making Process - Ekawestri Prajwalita Widiati (Universitas Airlangga, 2018)
Getting the public to participate in the government’s policy reflects a sense of control in democracy. However, constructing a mechanism of participation in legal provisions could be dilemma. It is important to realize that involving citizen in local government decision making particularly in law-making process has a fundamental difficulties; the essence of participation itself (openness and transparency) and the need to be efficient. This essay formulated an effective mechanism of public participation by juxtaposing steps in the local legislative process with the criteria of efficiency. This discussion is trying to encompass citizen participation from the initiation of a policy until it is enacted as a local legislation. Then in the next step, it will assess the elements that constitute an efficient drafting process. This article will consider such factors that are; financial cost; human resources or effort; wasted time; risk of failure; progress. The hypothesis is that not all of the means of public participation are efficient. The ideal notion of public participation put weighs on Local Authorities. What is needed to be underlined in this discussion is, to maximize the advantage of citizen involvement, it is important to look at the sequence where it should be held and what is the content. Moreover, the process of public participation should reflects principles namely: discovery, education, measurement, persuasion and legitimization.